An Overview of the Canadian Banking System: 1996 to 2015 - Robert McKeown (Queen's University, Department of Economics, 2017)
From 1996 to 2015, total assets at Canadian and foreign banks operating in Canada grew four-times in size. This growth occurred with neither a significant regulatory change, such as the repeal of Glass-Steagall, nor the introduction of new business lines, such as wealth management or investment banking. Using data from CANSIM and a little used dataset from OSFI, I describe how the Canadian banks earn revenue, fund business activities, and pay expenses. The success of the Canadian banking system can be attributed to: i) a focus on retail and branch-level banking, ii) a preference for deposit-financing, and iii) minimizing costs, particularly noninterest expenses. Furthermore, I provide a broad overview of the data, accounting rules, and trends in Canadian banking. Estimating a reduced form model similar to DeBoskey and Jiang (2012), I find no evidence that the Canadian banks manipulated the provision for credit losses to `smooth' earnings.
Keywords: G21; 330; Bank; Bank Lending; Borrowing; Commercial Banks; Financial Intermediaries; Retail Bank; Canada; Canadian